Legal Protection of Intellectual Property Rights in the Form of Trademarks on Mandatory Halal Food & Beverage (F&B) Products in Indonesia - Ofelica Ruth Mayca; July Esther; Jinner Sidauruk (Dinasti Research, 2025)
Indonesia, as the Country with the largest Muslim population in the world, has great potential in the halal food and beverage (F&B) Industry. Halal products not only fulfill the needs of Muslim consumers, but are an important part of cultural and religious identity. Intellectual Property Rights (IPR) protection plays a crucial role in encouraging innovation, protecting originality, and increasing the competitiveness of local products, especially in the F&B business sector. In the context of halal, halal certification has been made mandatory through Law 33 of 2014 concerning Halal Product Guarantee (JPH Law), which aims to provide legal certainty, safety, and convenience for consumers, while supporting the competitiveness of producers. This research explores the legal protection of brands in mandatory halal F&B products in Indonesia, by discussing the role of the government with related institutions and IPR protection in the face of global competition, as well as strategic steps to increase business actors' awareness of the importance of IPR and halal certification.